A Targeted Survey for Scrapie in Jos Plateau State, Nigeria. (31st July 2013) - Nwankiti, O. O.; Ikeh, E. I.; Arowolo, O. A.; Nwankiti, A. J.; Odugbo, M. O.; Seuberlich, T.
Abstract : Scrapie, a disease of sheep and goats with a progressive course and fatal outcome, has not been identified in Nigeria. Anecdotal scrapie reports by livestock workers abound. Livestock diseases like scrapie form huddles in livestock economics of countries. For 8 months we surveyed for scrapie targeting emergency/casualty slaughter sheep and goats in Jos, Nigeria. We clinically examined 510 sheep and 608 goats of local breeds, aged from 12 months to 5 years. In total 31 (5.10%) goats and no sheep were clinically suspicious for scrapie. Caudal brainstem tissues of suspect animals collected postmortem were analyzed for the disease specific form of the prion protein, PrP Sc, using Bio-Rad's TeSeE ELISA rapid test kit. No sample was positive for scrapie. Fluorescent antibody test for rabies and H&E staining on samples were carried out for differential diagnosis. These showed no pathological lesions indicative for neurological disease. While our findings do not exclude the presence of scrapie in Jos, we demonstrate that targeted sampling of small ruminants for neuroinfectious disease is feasible in developing countries, pointing to the possibility of implementing such a monitoring scheme in Nigeria to prevent economic losses in small ruminant livestock as scrapie caveats from endemic countries have shown.